Vínculos sonoros na diáspora: : investigando a teia de afetos entre migrantes e o rádio expandido - Maia , Bárbara (2021)
This paper investigates the affective bonds built through radio listening by Brazilians in diaspora conditions at Catalonia, Spain's semi-autonomous region, offering preliminary results of a doctoral internship held at the Universitàt Autònoma de Barcelona (UAB), between 2019 and 2020. It starts from the concept of expanded radio – which overflows from hertzian waves to multiple digital devices and platforms – and from the sociology of affection to discuss the extent to which this diasporic audience builds meaning for listening, in an identity affirmation process, of (re)connection with mother tongue and also negotiation to insert oneself in another culture. The research path includes a qualitative analysis of information gathered in 20 semi-structured interviews with Brazilians living in Barcelona, seeking to understand how they build meaning for sound communication and the extent to which expanded radio offers an in between place for migrants, mobilizing affections.